Visionary film; the American avant-garde, 1943-2000 - Adams Sitney, P. (Oxford : University Press, 2002)
- Meshes of the afternoon##- Ritual and nature##- The potted psalm##- The magus##- From trance to myth##- The lyrical film##- Major mythopoeia##- Absolute animation##- The graphic cinema: European perspectives##- Apocalypses and picaresques##- Recovered innocence##- Structural film##- The seventies##- The end of the 20th century.
boek